Bats adjust echolocation and social call design as a response to urban environments - Starik, Nicole; Göttert, Thomas (Frontiers in Ecology and Evolution, 2022)
Behavioral traits play a major role in the successful adaptation of wildlife to urban conditions. We investigated and compared the acoustic behavior of free ranging bats in rural (Havelland, Brandenburg) and urban (Berlin city center) green areas (n=6 sites) to assess possible effects of urbanization on bat vocalizations using automated real-time recordings from May-October 2020 and 2021. We show that foraging and social call activity of commonly occurring bat species was lower in urban areas compared to rural areas. We present data on rural-urban variation in acoustic parameters of echolocation and Type D social calls (produced during flight) using the example of the common pipistrelle Pipistrellus pipistrellus. Calls from urban sites revealed significantly higher end and peak frequencies compared to rural site calls. In addition, urban social calls present a higher degree of complexity as they structurally differed from rural social calls with regard to assemblage and number of call components. Moreover, urban social calls were emitted in a presumably different context than rural calls: antagonistic social calls in urban areas were detected throughout the year and in the acoustic absence of conspecifics and heterospecifics. Our results provide evidence for the ability of P. pipistrellus to modulate temporal and spectral features of echolocation and social calls, as well as patterns of social call production, in order to compensate for constraints imposed by the urban acoustic environment. We suggest that this acoustic behavioral plasticity plays a major role in the degree of adaptation of insectivorous bats to urban habitats.